WEED SPECIES ASSOCIATION IN ARABLE FIELDS: OLD APPROACH, NEW APPLICATION. (25th January 2018) - CONCENÇO, G.; ANDRES, A.; SCHREIBER, F.; MOISINHO, I. S.; CORADINI, M. C.; MARTINS, M. B.
SUMMARY: We aimed to assess the potential of the characterization of association among weed species as a tool to understand weed occurrence for further supporting long-term management programs. After a sequence of summer crops, which included irrigated rice and sorghum, the experimental area was submitted to subsoiling, limestone was applied, and ryegrass was planted in the winter season. Six months later, an ACCase-inhibitor herbicide was used to select only non-grassweed species. Field survey was carried out on 100 quadrats with 0.5-m width that were randomly sampled. Plant species were organized in 2 × 2 contingency tables. The results of the calculated chi-squares were compared to the respective tables, and results were presented as a paired chi-square matrix. The species–area curve was also obtained. The relative occurrence of species was determined by its frequency and presented as a wordcloud. The network analysis was obtained by using the Fruchterman–Reingold layout. The hypothesis of plant association aiming survival in arable fields was validated. The methodology of plant association based on the chi-square test was applicable to arable fields, where weed species (usually competitor plant types) occur in clusters. From a practical point of view, preference should be given to herbicides that are efficient on most species within a given cluster.